IMPLEMENTATION OF STEAM ELEMENTS INTO THE EDUCATIONAL PROCESS OF NATURAL SCIENCES - Orlova, Olha Volodymyrivna; Lahutenko, Oksana Tarasivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article highlights the features of using STEAM elements in the educationalprocess of teaching biology and ecology.